L'Archivio privato D'Avalos The D'Avalos Private Archive - Flavia Luise (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2012)
The D'Avalos name evokes images of cruel battles and tragic love stories, reminds figures of great warlords and sophisticated ladies, nourishes the legend of fabulous riches and luxurious residences. The work of scholars who explored the thick forest of Innico and Alfonso D'Avalos descendants do not allow to completely outline the history of this family. The family's private archive, inviolable guardian of their memories, where records related to the private sphere and official acts, such as pontifical papers and relations with the sovereigns, are kept is still inaccessible. The records of the notary Scotto di Santolo can be very useful, because they allowed the reconstruction of the wide archival heritage coming from the past, recorded along with other property of the family after the death, in 1862, of last heir of the primary branch, the Prince Alfonso D'Avalos. The transcription of the D'Avalos archive before the Italian unification that we present can avoid its definitive "burial".